2015
DOI: 10.3389/fpls.2015.01083
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Compost Management Influence Maize (Zea mays) Productivity Under Semiarid Condition with and without Phosphate Solubilizing Bacteria

Abstract: Phosphorus (P) unavailability and lack of organic matter in the soils under semiarid climates are the two major constraints for low crop productivity. Field trial was conducted to study the effects of P levels, compost application times and seed inoculation with phosphate solubilizing bacteria (PSB) on the yield and yield components of maize (Zea mays L., cv. Azam). The experiment was conducted at the Agronomy Research Farm of The University of Agriculture Peshawar-Pakistan during summer 2014. The experiment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…The effects of PGP bacteria on annual crops have also been the focus of research (Bashan et al 2014 and references therein). For instance, phosphate-solubilizing bacteria were shown to be effective in enhancing maize yields (Khan and Khan 2015). Our data extend understanding of the role played by PGP bacteria at the field level in arboreal plants, such as grape.…”
Section: Discussionsupporting
confidence: 49%
“…The effects of PGP bacteria on annual crops have also been the focus of research (Bashan et al 2014 and references therein). For instance, phosphate-solubilizing bacteria were shown to be effective in enhancing maize yields (Khan and Khan 2015). Our data extend understanding of the role played by PGP bacteria at the field level in arboreal plants, such as grape.…”
Section: Discussionsupporting
confidence: 49%
“…One major reason for low rice yield in Pakistan is imbalanced nutrient application (Amanullah and Hidayatullah, 2016 ; Amanullah and Inamullah, 2016a , b ). Integrated use of chemical fertilizers along with organic manure has been widely recommended for sustaining agricultural production in Northwest Pakistan (Amanullah and Inamullah, 2015 ; Amanullah and Khan, 2015 ; Amanullah and Khalid, 2016 ). Improved management practices such as incorporation of crop residue, animal manures along with chemical fertilizers application increase soil organic carbon and improve crop productivity (Six et al, 2002 ; Vanden et al, 2003 ; Rakshit et al, 2008 ; Amanullah and Hidayatullah, 2016 ; West and Post, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is always inadequate under rice based system in Northwest Pakistan to meet the requirement of rice plants (Amanullah and Inamullah, 2016a , b ). Recent research conducted on different field crops suggested that low organic matter content (Materechera, 2010 ; Verhulst et al, 2011 ; Enujeke, 2013 ; Hidaytaullah and Amanulla, 2015 ; Iqbal et al, 2015 ; Amanullah and Hidayatullah, 2016 ; Amanullah and Khalid, 2016 ) and low availability of phosphorus (Garg and Bahla, 2008 ; Alam et al, 2009 ; Bakhsh et al, 2012 ; Rasavel and Ravichandran, 2013 ; Yoseftabar, 2013 ; Amanullah and Khan, 2015 ; Amanullah and Inamullah, 2016a , b ; Amanullah and Khalid, 2016 ) reduce crop productivity all over the world. Integrated use of mineral phosphorus along with animal manures or plant residues can improve rice growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Number of seeds ear −1 was calculated on ten randomly selected ears from each plot and then average was worked out. Data on number of ears 100 plants −1 was calculated by counting number of ears in 100 plants and then it was averaged (Amanullah and Khan, 2015). ” Three central rows of each treatment was harvested the material was dried and converted into biological yield (kg ha −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The reasons for low crop productivity in semiarid climate are: (1) low soil moisture availability (2) low soil fertility (Amanullah et al, 2012), and (3) indiscriminate use of chemical fertilizers by smallholders (Amanullah et al, 2015a). According to Oad et al (2004) and Amanullah and Khan (2015), the major problems in the way of increasing yield at farmer's fields are the inappropriate nutrients supply. Among the plant nutrients, nitrogen (N) management is one of the most important factor required for improving crop productivity and profitability under semiarid climates (Amanullah, 2016).…”
Section: Introductionmentioning
confidence: 99%